(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
One of the important tasks carried out by forensic medicine expert apart from conducting autopsies is estimation of age in living where there is no proof of age or the proof available is not authentic. The present study analyse the profile of medico-legal age estimation cases brought to the department of forensic medicine of a medical college and hospital of rural Haryana. Retrospective data of five years was extracted from records maintained in the office and analyzed. All medico-legal cases brought for age estimation were included and all civil cases were excluded. A total of 116 individuals were brought for age estimation during the study period. Among those examined, maximum were male, accused and were from rural background. The majority of victims were female children. The findings should draw the attention of doctors and healthcare workers to the problem of juvenile crimes by or against children and encourage them to work together with law enforcement and social organizations in securing justice.